Visual quantitative analysis of hot literature on interstitial lung diseases based on Web of Science database - Zhi-Jun FAN; Jia-Hui LI; Qiao WANG; Jia-Ming CAO; Hui-Yuan LIU; Yue-Lin ZHANG; Ling-Yu FU (Yixue xinzhi zazhi)
Objective To make a visual bibliometric analysis of the development trend of interstitial lung diseases and research hotspots in international fields, and to provide reference information for the development of interstitial lung diseases research in China.Methods Using Citespace 5.5 software and Web of Science database as data source, the year, country, journal and keywords of interstitial lung diseases published in recent ten years were analyzed visually.Results A total of 6098 literatures were retrieved, and the number of articles published has gradually increased since 2011. The country with the largest number of articles published is the United States, the highest cited rate of journal is AM J RESP CRIT CARE, and the authors with the highest number of articles and citations are Toby M Maher and Raghu G, respectively. The research focus in this field are epidemiology, inflammation and pathogenesis, diagnosis and treatment.Conclusion The international attention and research level of interstitial lung disease are increasing recently. Exploring the research hotspot and development trend in this field can provide direction and basis for China to keep up with the international research trend of interstitial lung disease.